TRANSFORMATION OF THE POST-MERGER SHARIA BANKING BUSINESS MODEL: A STAKEHOLDER PERSPECTIVE - Watiningsih, Ferdina (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the business model transformation of Bank Syariah Indonesia post-merger from a stakeholder perspective and its impact on Islamic banking performance. The research employs a qualitative approach with a case study design involving 47 informants from various stakeholder groups, with data collected through in-depth interviews, participant observation, and document analysis. The results identify five main dimensions of transformation: value proposition, operational architecture, digital ecosystem, organizational culture, and sharia compliance. Stakeholder perspectives show significant diversity with management remaining optimistic despite cost synergy realization of only 52%, while employees experience perception polarization and retail customers complain about service quality decline. Performance impact demonstrates a J-curve pattern with ROA increasing from 0.95% to 1.28%, BOPO decreasing to 81.76%, and MSME financing increasing to 60.2%. The study concludes that transformation requires optimal balance among stakeholder interests and a holistic approach considering financial, operational, social, and sharia compliance dimensions.